Metabolomics-based diagnosis and prognosis of dengue virus infections and NS1 antigen detection for diagnosis and surveillance in humans and mosquitoes - Voge, Natalia Victoria, author; Blair, Carol D., advisor; Beaty, Barry J., advisor; Loroño-Pino, Maria A., committee member; Eisen, Lars, committee member; Belisle, John T., committee member; Prenni, Jessica E., committee member (Colorado State University. Libraries, 2013)
Dengue (DEN) is a mosquito-borne viral disease of significant public health importance. There are currently no commercialized vaccines or accepted pharmacological treatments for DEN disease, making mosquito surveillance critical for the prevention of outbreaks of this disease. Aedes aegypti is the principal vector of DENV, although Aedes albopictus and other Aedes species have been reported to be able to transmit it. Improved surveillance methods for DENV in mosquito populations would be of great value for public health and vector control programs and would provide better risk assessment of potential DENV infections in humans. Improved mosquito-based surveillance would also improve vector control programs by targeting areas at higher risk for ongoing or potential epidemics for vector control. Non-structural protein 1 (NS1) detection by ELISA is a commercially available test with the ability to detect DENV NS1 protein in DENV infected samples. Studies were conducted to determine the ability of the NS1 antigen test to detect DENV in Aedes aegypti mosquitoes. The NS1 antigen detection test proved to be highly sensitive and specific for DENV-antigen detection in pools of mixed infected and non-infected mosquitoes under various field-simulated conditions and in different sizes of mosquito pools. This test could facilitate mosquito-based surveillance for early warning of DEN outbreaks. The capacity of this test to diagnose human DENV infections in non-invasive clinical specimens, i.e., urine and saliva, was also investigated. NS1 protein detection in acute phase, non-invasive clinical specimens was found to be less sensitive than NS1 detection in serum samples. Most dengue virus (DENV) infections are subclinical. The clinical manifestations of apparent infections range from DEN fever (DF), typically a self-limiting illness with fever and rash, to severe DEN hemorrhagic fever and shock syndrome (DHF/DSS). Upon presentation, there is no way to predict whether or not the patient will experience DF or will progress to the severe form of disease (DHF/DSS). A sensitive and specific test that utilizes acute phase clinical specimens and that provides diagnosis of DENV infection as well prognosis of progression to severe disease is sorely needed. Such a test would permit identifying those patients destined for severe disease for appropriate patient management and therapeutic intervention. An innovative metabolomics platform was used in these studies to determine a biosignature of small molecular biomarkers (SMBs) that can potentially differentiate patients with the most severe forms of disease from DF and non-DEN patients. SMBs that could potentially be diagnostic of DENV infections and prognostic of disease outcomes were identified in acute phase serum, saliva, and urine specimens obtained from DEN and non-DEN patients from Mexico and Nicaragua. Using acute phase serum specimens, a panel of six candidate SMB compounds was identified by tandem liquid chromatography-mass spectrometry (LC-MS/MS); five of these six biomarkers differentiated DF patients from those with DHF/DSS and have potential to diagnose and predict DEN disease or DEN severity (DHF/DSS) outcomes. Two candidate SMB compounds were identified in urine and one in saliva that could potentially be used for diagnosis and prognosis of DEN infections. Tandem mass spectra of candidate compounds and commercial standards were obtained and compared to identify the SMB metabolites. Some of the SMB identities were confirmed by using the NIST (National Institute of Standards and Technology) or METLIN spectrum libraries. The biochemical nature of the identified metabolites included phospholipids, fatty acids, amino acids, nucleosides, and vitamin D. These SMBs have potentially important roles in DEN pathogenesis and in endothelial cell metabolism (these cells are among the principal target cells affected during severe DEN disease). The immediate goal of this dissertation research was to identify a biosignature panel of LC-MS/MS-identified candidate SMB metabolites that differentiate the DEN disease diagnosis groups (DHF/DSS, DF, and ND) and that have potential for diagnosis and prognosis of DENV infections using acute phase serum and non-invasive clinical specimens. However, it is unlikely that LC-MS/MS technology will be applicable in the front-line clinics where DEN patients first present. Thus a long-term goal of the research project is to select a subset of these pathogenically and physiologically relevant SMBs and then determine the potential for the metabolite analyte or a surrogate (e.g., a protein involved in the metabolic pathway conditioning the metabolic change) to be incorporated into diagnostic formats amenable to point of care tests (POC), such as ELISA based formats. A diagnostic algorithm incorporating results from such a POC test and conventional laboratory and clinical biomarkers could provide dramatically improved capability for diagnosis and prognosis of DENV infections and would be of immense value to physicians in managing patients.
Keywords: mosquitoes; metabolomics; diagnosis; Dengue